BIODEGRADASI ZAT WARNA ACID ORANGE 7 MENGGUNAKAN ENZIM JAMUR TIRAM PUTIH (PLEUROTUS OSTREATUS) - Achmad Amiruddin; Hasri Hasri; Sudding Sudding (Universitas Airlangga, 2018)
Synthetic dyes is most be usedin the textile industry because it is stable, easy to obtain, and cheap,the waste, however,is difficult to degrade, so it can cause contaminants in the waters and disrupt the aesthetics of water bodies. One of the alternative and environmentally-friendly methods that can be used to degrade dyestuff waste prior to discharge into the waters is by utilizing microorganisms as degrading agents. Therefore, this study aims to determine the ability of P.ostreatus fungus enzymes in degrading acid orange dyes 7 based on the variation of degradation time. The results showed that P.ostreatus fungus enzyme was able to degrade the orange acid 7 until 59.36% Keywords: degradation, acid orange 7, white oyster mushroom (P.ostreatus)